Influence of loading parameters in cyclic tension-compression regime on crack-bridging behaviour of PVA microfibres embedded in cement-based matrix. (20th December 2019) - Ranjbarian, Majid; Mechtcherine, Viktor
Highlights: A new double-sided fibre pull-out test setup is used for cyclic experiments. Different pull-out behaviours characteristic to cyclic loading are categorized. Various fibre damage types are found in cyclic tension-compression regime. A quantification approach for the fibre performance under such conditions is suggested. Compressive stress component causes an increase in fibre deterioration. Abstract: The mechanical performance of fibre-reinforced cement-based materials may considerably vary depending on the particular loading scenario. The article at hand investigates the effect of the loading parameters in cyclic tension-compression regime on bridging behaviour of aligned short PVA microfibres in cement-based matrix. Under such loading, microfibres suffer damages between crack flanks, and their bridging capacity decreases. To understand the damage processes in conjunction with the degradation of fibre bridging capacity, cyclic fibre pull-out tests were performed with subsequent damage analysis of the fibre. The influence of the cyclic regime on the bridging behaviour of single PVA microfibres was comprehensively studied. The results clearly showed a reduction of bridging capacity with an increase in the number of cycles and in the compression level in a reversed tension-compression loading regime. Based on these findings a damage quantification approach is suggested.